Dolphin Shows and Interaction Programs: Benefits for Conservation Education?. Issue 1 (23rd May 2012) - Miller, L.J.; Zeigler‐Hill, V.; Mellen, J.; Koeppel, J.; Greer, T.; Kuczaj, S.
<x xml:space="preserve">Abstract</x> Dolphin shows and dolphin interaction programs are two types of education programs within zoological institutions used to educate visitors about dolphins and the marine environment. The current study examined the short‐ and long‐term effects of these programs on visitors' conservation‐related knowledge, attitude, and behavior. Participants of both dolphin shows and interaction programs demonstrated a significant short‐term increase in knowledge, attitudes, and behavioral intentions. Three months following the experience, participants of both dolphin shows and interaction programs retained the knowledge learned during their experience and reported engaging in more conservation‐related behaviors. Additionally, the number of dolphin shows attended in the past was a significant predictor of recent conservation‐related behavior suggesting that repetition of these types of experiences may be important in inspiring people to conservation action. These results suggest that both dolphin shows and dolphin interaction programs can be an important part of a conservation education program for visitors of zoological facilities. Zoo Biol. 32:45‐53, 2013. © 2012 Wiley Periodicals, Inc.